Selection and co-selection of antimicrobial resistance in gut enterococci of swine and cattle fed diets supplemented with copper, tylosin, and chlortetracycline - Amachawadi, Raghavendra G. (Kansas State University, 2014)
Copper, as copper sulfate, is often used as an alternative to in-feed antibiotics for growth promotion in both swine and cattle diets. Gut bacteria exposed to copper can acquire resistance, which among enterococci is conferred by a plasmid-borne transferable copper resistance gene (tcrB). The plasmid also carries tetracycline [tet(M)] and macrolide [erm(B)] resistance genes. Because of the genetic link between acquired copper (tcrB) and antibiotic resistance in Enterococcus spp., we hypothesized that copper supplementation may exert selection pressure for enterococci to become resistant to macrolides and tetracyclines, and possibly to other antibiotics. We conducted studies in cattle and swine to investigate the relationship between copper supplementation and the fecal prevalence of tcrB-positive enterococci, as well as its potential co-selection for macrolide and tetracycline resistance. The prevalence was higher in animals fed diets supplemented with elevated level of copper compared to normal level (P < 0.05). The tcrB-positive isolates belonged to either E. faecium or E. faecalis; the majority was E. faecium. All tcrB-positive isolates also contained both erm(B) and tet(M) genes; however, none of them harbored the vanA gene. Median minimum inhibitory concentrations (MIC) of copper for tcrB-positive and tcrB-negative enterococci were 22 mM and 4 mM, respectively (P < 0.0001). The overall prevalence of erm(B) and tet(M) genes among enterococcal isolates of cattle were 46.8 % and 57.5%, respectively; in contrast,100% of the swine isolates were positive for both erm(B) and tet(M) genes. The transferability of the tcrB gene was demonstrated by filter mating assay. Multi-locus variable number tandem repeat analysis revealed a genetically diverse population of enterococci. The finding of a strong association between the copper resistance gene and other antibiotic (tetracycline and tylosin) resistance determinants is significant because enterococci are potential pathogens and have the propensity to transfer resistance genes to other bacteria in the gut. The occurrence of vancomycin resistant enterococci in swine in the US is very rare. Strains of E. faecium positive for vanA, that confers resistance to vancomycin, were isolated and characterized from swine feces. The swine strains belonged to clonal complex 17, a well-adapted hospital clone throughout the world.
Keywords: Antimicrobial resistance; Cattle; Copper; Enterococcus spp.; Swine; Antibiotics; Epidemiology (0766); Microbiology (0410)